European Doctoral Program in Quantitative Economics: The London School of Economics, Rheinische Friedrichwilhems Universitat Bonn, Universite Catholique de Louvain (Review of Economic Studies, 1978)
European Doctoral Program in Quantitative Economics: The London School of Economics, Rheinische Friedrichwilhems Universität Bonn, Université Catholique de Louvain The Review of Economic Studies, Volume 45, Issue 1, February 1978, Pages 213–214, https://doi.org/10.2307/restud/45.1.213-a Published: 01 February 1978